The Correlations among Parents’ Socioeconomic Status, the Twelfth Grade Students’ Language Learning Attitude and English Achievement - Lisda Enny Noprianty (Jurnal Bahasa dan Sastra, 2020)
Abstract: This paper was aimed at finding out whether or not (1) there was a correlation be- tween parents’ socioeconomic status and the twelfth grade students’ English achievement, (2) there was a correlation between students’ language learning attitude and English achievement (3) there was a correlation between parents’ socioeconomic status and students’ language learn- ing attitude, and (4) there were contributions of parents’ socioeconomic status and, students’ language learning attitude simultaneously toward students’ English achievement. The data were collected through questionnaires and school documentation. From the population of 579 twelfth grade students in Academic Year of 2019/2020, the writer chose 119 (20%) students as the sample by using proportional random sampling method. The result showed that there was a sig- nificant correlation between parents’ socioeconomic status and English achievement (r=595); there was a correlation between students’ language learning attitude and English achievement (r=622); there was a correlation between parents’ socioeconomic status and students’ language learning attitude (r=4.340) and there were contributions of parents’ socioeconomic status, and students’ attitude simultaneously toward students’ English achievement simultaneously, with R square value was 0.929. It meant that the variability of English achievement could be explained at a percentage of 92.9% by parents’ socioeconomic status and students’ attitude. Keywords: parents’ socioeconomic status, students’ language learning attitude, and English achievement Abstrak: Penelitian ini bertujuan untuk mengetahui apakah (1) ada hubungan antara status sosial ekonomi orang tua dengan prestasi belajar bahasa Inggris siswa kelas dua belas, (2) ada hubungan antara sikap belajar bahasa siswa dengan prestasi belajar bahasa Inggris (3) ada hubungan antara status sosial ekonomi orang tua dengan sikap belajar bahasa siswa, dan (4) ada kontribusi status sosial ekonomi orang tua dan sikap belajar bahasa siswa terhadap prestasi bahasa Inggris siswa. Pengumpulan data dilakukan melalui kuesioner dan dokumentasi seko- lah. Dari populasi 579 siswa kelas XI tahun pelajaran 2019/2020, penulis memilih 119 (20%) siswa sebagai sampel dengan menggunakan metode proporsional random sampling. Hasil pe- nelitian menunjukkan bahwa ada hubungan yang signifikan antara status sosial ekonomi orang tua dengan prestasi belajar bahasa Inggris siswa kelas XII (r = 595); ada hubungan antara sikap belajar bahasa siswa dengan prestasi bahasa Inggris (r = 622); Ada hubungan antara status so- sial ekonomi orang tua dengan sikap belajar bahasa (r = 4,340) dan ada kontribusi status sosial ekonomi orang tua dan sikap siswa terhadap prestasi belajar bahasa Inggris siswa secara simul- tan, dengan nilai R square 0,929. Artinya variabilitas prestasi bahasa Inggris dapat dijelaskan92,9% oleh status sosial ekonomi orang tua dan sikap siswa Kata-kata kunci: status sosial ekonomi orang tua, sikap belajar bahasa siswa, dan prestasiBahasa Inggris